2000
DOI: 10.1093/gerona/55.4.b177
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Stress Associated With Concentric and Eccentric Isokinetic Exercise in Young and Older Adults

Abstract: Heart rate (HR), mean arterial blood pressure (MAP), and rate-pressure product (RPP) responses to submaximal isokinetic concentric (CON) and eccentric (ECC) knee extension exercise were compared at the same absolute torque output in 20 young (mean+/-SD=23.2+/-1.7 years) and 20 older (mean+/-SD=75.2+/-4.6 years) adults. After determination of peak CON and ECC torques, subjects performed separate, randomly ordered, 2-minute bouts of isokinetic CON and ECC exercise (90 degrees/s, exercise intensity: 50% of CON pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
2
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 34 publications
11
81
2
13
Order By: Relevance
“…These results are in accordance with Haennel et al 14 and Overend et al 39 and are in conflict with others 2,3,25-28 which verified higher HR values during concentric rather than eccentric exercise. It is well known that the HR acceleration observed as a result of a muscular contraction occurs due to a vagal withdrawal, primarily in the beginning of the voluntary effort (i.e., 10 sec.)…”
Section: Discussionsupporting
confidence: 79%
“…These results are in accordance with Haennel et al 14 and Overend et al 39 and are in conflict with others 2,3,25-28 which verified higher HR values during concentric rather than eccentric exercise. It is well known that the HR acceleration observed as a result of a muscular contraction occurs due to a vagal withdrawal, primarily in the beginning of the voluntary effort (i.e., 10 sec.)…”
Section: Discussionsupporting
confidence: 79%
“…Apesar do No que se refere à resposta hemodinâmica aguda do exercício físico, um dos fatores que influenciam no aumento da PA é o aumento da FC. 13 Conforme pode ser observado na Tabela 2 Distribuição da frequência cardíaca na avaliação inicial e final dos idosos praticantes de atividades físicas nas academias da terceira idade. Tabela 4 Distribuição da pressão arterial sistólica na avaliação inicial e final dos idosos praticantes de atividades físicas nas academias da terceira idade.…”
Section: Discussionunclassified
“…4 após um programa sistematizado de atividades físicas durante seis meses na ATI, verificaram importantes reduções nos níveis pressóricos, o que foi relatado inclusive pelos próprios usuários. As modalidades de exercícios realizados nas ATI no momento da pesquisaconsiderando o tipo de contrações realizadas (predominantemente dinâmicas), a moderada carga externa (peso do próprio corpo e dos equipamentos) e o número reduzido de grupos musculares solicitados simultaneamente 13 -podem explicar a menor resposta fisiológica ao esforço.…”
Section: Discussionunclassified
“…Literature has shown more concern in addressing the effects of resistive exercises practiced in an appropriate equipment. Some examples are the studies of Overend et al 11 and Smolander et al 25 , who focused their attention on cardiovascular stress of youngsters and elders during isokinetic and isometric exercises, respectively. The results of this study showed there was no significant HR differences between continuous and intermittent sets with similar or different number of repetitions, showing that the proposed workout situations did not influence the response of this variable.…”
Section: Fig 4 -Blood Pressure Response In Continuous and Intermittementioning
confidence: 99%
“…One of the aspects to be considered is the safety of the proposed activities, particularly on acute cardiovascular responses. For this purpose many authors have used assessment of heart rate (HR), blood pressure (BP), and rate-pressure product (RPP) as non-invasive indicators of cardiovascular overload during exercise [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%